Experimental languages ​​of plastic representation through new technologies - Luis Eduardo Motta (Corporación Universitaria Minuto de Dios, 2011)
Technology is one of the important factors in artistic creation, the relationship of traditional art through its different periods, the evolution of new technologies and their use in contemporary art, the development of video art, digital photography, computer, video conference, cell phone, virtual images, multimedia facilities, internet and new storage media among others, are added to make way for new artistic expressions and complex communication channels and networks, stimulating complexity of novelty and imagination. The world of artificial universes image and give way to new forms, transforming artistic expression such as music, visual arts, theater, dance, among others, looking as if our society entered a true mutation.